(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This paper investigates the effect of guided inquiry and lecture methods on students’ academic achievement in biology in senior secondary schools in Rivers State. Two research questions and two null hypotheses tested at 0.05 level of significance guided the study. The sample of the study was 407 SSII biology students drawn by Purposive sampling technique in which four schools were selected from eight senior secondary schools in the area of study. The sample consisted of 223 boys and 184 girls. The classes used for the study were selected by simple random sampling using the ballot system. Mean, grand mean, standard deviation and t-test statistic were used to analyze data from the result of Biology Achievement Test used for data collection. The result shows that mean pretest scores of the experimental and control groups used for the study are insignificant. The mean posttest scores show a wide difference. There is a significant difference between the achievements of students taught with guided inquiry and those taught with lecture method in favour of guided inquiry. Guided inquiry proved more effective than lecture method in enhancing students’ academic achievement in biology. Recommendations are made from the findings of the study.